Snake models for offline signature verification: a comparative study. (27th August 2009) - Velez, J.F.; Sanchez, A.; Moreno, B.; Esteban, J.L.
This paper presents an experimental comparison of different hybrid snake-based algorithms for automatic offline signature verification. Offline signature verification aims to establish the degree of similarity between one given test signature and one reference signature. Our work aims to study how effective introducing fuzziness to tackle this image analysis problem. We developed several hybrid (crisp and fuzzy) snake algorithms adapted to the practical requirements of automatic signature verification. Our work compares different hybrid snake approaches for this verification problem.